Beberapa Faktor yang Berhubungan dengan Penggunaan Sistem Informasi oleh Penyuluh KB terhadap Kelengkapan Laporan Kampung KB di Kota Semarang - Novita Triani; Yudhy Dharmawan; Dharminto Dharminto; Atik Mawarni (Jurnal Kesehatan Masyarakat, 2019)
Secondary data of Kampung KB report showed that the lack of use of Kampung KB information system was due to the lack of user’s motivation and self confidence, thus encouraging incomplete reports of Kampung KB. The purpose of this study is to analyze several factors related to the use of web based information system to Kampung KB report completion. This study was an explanatory research. Study population were family planning counselors and the sampling technique was total sampling. Research analysis were univariate and bivariate. Univariate analysis showed that the completeness of Kampung KB reports varies from 0% to 100% which is only 28,6% categorized as complete. Bivariate analysis showed that there are correlation between perceived ease of use, self confidence, dan motivation with the use of Kampung KB information system (pvalue < 0,05). But there are no correlation between perceived ease of use, self confidence, dan motivation with reports completeness through the use of information system as an intervening variable (pvalue > 0,05). This study provides suggestions to improve user’s skill, self confidence, and motivation in using Kampung KB information system through training and supervising.